MATERNAL EMERGENCY: A STUDY OF HUMAN RIGHTS IN A NATIONAL LAW PERSPECTIVE - Istirochah Istirochah (Universitas 17 Agustus 1945 Semarang, 2021)
A maternal emergency is a condition that threatens the life of pregnant women, both in the process of pregnancy, childbirth, and postpartum. Notes from the National Population and Family Planning Board (BKKBN) that in 2019 there were approximately 4,100 cases of maternal mortality, while in 2020, there were approximately 4,400 cases. These conditions must be minimized to guarantee human rights for mothers. Meanwhile, as a constitutional state characterized by the protection and recognition of human rights, Indonesia has special regulations regarding human rights in the form of Law Number 39 of 1999. Based on these facts, a problem is formulated: protecting human rights against maternal emergencies in Law Number 39 of 1999. The type of research used is normative juridical. The data used is secondary data. The data analysis used is qualitative. The results of the discussion of this article, namely, the protection of human rights against maternal emergencies, is defined as a protection of human rights for mothers who have the potential to experience death during pregnancy, childbirth, and postpartum. The protection is regulated in Article 4, 9 paragraph (1), 41 paragraph (2), and 49 paragraph (2) of Law Number 39 of 1999. In this case, the article is divided into two classifications. First, Article 4 and Article 9 paragraph (1) concerning the right to life. Second, Article 41 paragraph (2) and 49 paragraph (2) concerning women’s health rights.